The Evolution of the Leibnizian Notion of "Primary Matter" and its Scholastic Background - Ruiz Gómez, Leonardo (Cauriensia, 2024)
This paper aims to clarify the evolution of the notion of primary matter in Leibniz’s philosophy. The analysis takes the scholastic discussion on the reality of primary matter as a framework to explain the development of Leibniz’s ideas. It will be shown that Leibniz argued in his earlier writings for a conception of primary matter as some sort of being (similarly in line with some scholastic philosophers like Scoto, Ockam, and Suarez). In contrast, in his mature metaphysics, he deployed this primary matter of reality, approaching Aquinas’s position in a creative and novelty manner.